The production and circulation of agricultural knowledge as interrogated by agroecology - Claude Compagnone; Claire Lamine; Lucie Dupré (Revue d'anthropologie des connaissances)
The goal of this article is to consider to what extent the promotion of agroecology in France is reopening questions of the production and circulation of agricultural knowledge. First, a brief historical review allows us to show how the institutionalization of agroecology has emerged as a major transformation operator within the contemporary agricultural scene. Next, we consider changes in modes of knowledge construction and exchange as they relate to the emergence of agroecology from three perspectives: in terms of the singular and local nature of this knowledge; in terms of how local knowledge is articulated and shared; and in terms of the tension between encapsulated knowledge and embodied knowledge. Finally, the papers collected in this issue are briefly presented, with special attention to the forms of knowledge distribution they make visible, across different spaces and between and among different social actors.